2006
DOI: 10.1073/pnas.0511125103
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of the subtectorial space caused by electromechanics of cochlear outer hair cells

Abstract: The stereocilia of the cochlear inner hair cells (IHCs) transduce vibrations into the sensory receptor current. Until now, mechanisms for deflecting these stereocilia have not been identified experimentally. Here, we identify a mechanism by using the electromechanical properties of the soma of the outer hair cell to produce an intracochlear, mechanical force stimulus. It is known that the soma of this cell generates mechanical force in response to a change of its transmembrane potential. In the present experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
154
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(165 citation statements)
references
References 59 publications
11
154
0
Order By: Relevance
“…Previous publications have shown that 9AC reduces the electromechanical response of the organ of Corti [9,14] and the magnitude of the imaginary component of the axial mechanical impedance of the isolated OHC [1]. As a result of showing that 9AC also reduces the NLC of prestin-transfected HEK293 cells, we conclude that 9AC directly interacts with the motor protein prestin.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous publications have shown that 9AC reduces the electromechanical response of the organ of Corti [9,14] and the magnitude of the imaginary component of the axial mechanical impedance of the isolated OHC [1]. As a result of showing that 9AC also reduces the NLC of prestin-transfected HEK293 cells, we conclude that 9AC directly interacts with the motor protein prestin.…”
Section: Discussionsupporting
confidence: 67%
“…The impedance was manipulated pharmacologically with the voltage-dependent chloridechannel blocker 9AC, which is known to reduce the electrically induced motion of the organ of Corti [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the vibration decrease observed at OHC1 defies any obvious explanation, but a somewhat similar behavior was reported for alternating current stimulation at acoustic frequencies [17]. Nowotny et al showed that the RL at the inner hair cell vibrated in antiphase to OHC2 and suggested a pivot close to the pillar head.…”
Section: Discussionsupporting
confidence: 58%
“…Electrically evoked displacements of the TM reported in this study have important implications for cochlear preparations in which electrical stimulation is applied [2,11,12]. Mechanical responses to electrical stimulation generally have been attributed to OHC somatic and hair bundle motility mechanisms.…”
Section: Implications For Electrical Stimulation Studiesmentioning
confidence: 72%